Molecular survey on the parasitic nematode Contracaecum spp. in fish (Planiliza abu) destined for human consumption - Alali Firas; Hussein Muayad A.; Jawad Marwa (Veterinarski Glasnik)
Contracaecum spp. is a parasitic nematode belonging to the Anisakidae family and which has a significant potential zoonotic effects on different hosts. Anisakiasis in humans is caused due to consumption of raw infected or undercooked seafood that contains nematode larvae. In this study, the prevalence of Contracaecum spp. nematodes in the fish, Planiliza abu, was determined over eight months from June 2022 to January 2023. The source of fish was Razzaza Lake, while the specimens of Planiliza abu were purchased from the local market, Karbala city, Iraq. The Contracaecum spp. nematodes were examined by morphological and molecular techniques.The total prevalence was 32%, as 133 of 416 fish were infected in the viscera by Contracaecum spp. third stage (L3) larvae. Molecular diagnosis of the COX-2 gene in Contracaecum spp. from P. abu was used to confirm the infection and to study their population biology. In the parasitology laboratory of the Veterinary Medicine College at Kerbala University, we confirmed the nematodes morphologically and molecularly as Contracaecum spp. The infection rates in September and November were greater than in October 2022. The results showed a significant positive correlation between the length of the fish and the number of nematodes per fish. This study detected the presence of Contracaecum spp. using analysis of mitochondrial cytochrome c oxidase II (COX-2 gene). In conclusion, molecular genotyping might be an effective method for detecting the Contracaecum L3 larval species, determining the biology of the life-cycles, population structures, transmission methods, and intermediate hosts types.